Optimization of drill method to overcome the problem of Arabic writing errors - Waro, Ruhamaul; Ulum, Mohammad Samsul; Zuhdy, Halimi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Imla is one of the important skills in learning Arabic. However, many students have difficulty writing correctly, in writing letters, punctuation, and grammar. This ability often hinders students' ability to master Arabic in its entirety. Therefore, this study aims to optimize the application of the drill method (Repetitive exercise) in imla' learning as a solution to overcome this problem. This research is a literature study with data sources from scientific journals and books related to research. The study results show that linguistic problems in imla' learning is caused by students' lack of understanding of the rules of imla', such as writing similar letters, writing ta', and writing hamzah. In addition, the mother tongue is also one of the factors that cause students to have difficulty transliterating the speech they hear. The way to optimize the drill method to overcome Arabic language problems, especially in writing, is to determine specific learning objectives, select practice materials that suit the needs and abilities of learners, and vary drill method techniques with other learning techniques or methods.